2018
DOI: 10.1038/s41598-018-28797-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pancreatic pathology in Plasmodium falciparum malaria patients

Abstract: Hypoglycaemia is an important complication of Plasmodium falciparum malaria infection, which can be lethal if not treated. A decrease in blood sugar (BS) level has been correlated with disease severity, parasitaemia and the use of certain antimalarial drugs. This study explored the relationship between pancreatic pathology, including the expressions of insulin and glucagon in the islets of Langerhans, and the BS levels in P. falciparum malaria patients. Pancreatic tissues from malaria patients were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Using a combination of bioluminescence and IVM, we confirmed that the g-WAT is a major parasite reservoir (Trindade et al, 2016), and we identified a previously unknown reservoir: the pancreas. Previous works on T. cruzi (Corbett et al, 2002;Dufurrena et al, 2017;Martello et al, 2013), Plasmodium (Abhilash et al, 2016;Glaharn et al, 2018), and Toxoplasma (Nassief Beshay et al, 2018) have reported sequestration in pancreatic blood vessels, pancreatic invasion, and morphological changes in the pancreas, including acute pancreatitis in humans. The fact that the pancreas represents one of the largest reservoirs of an extracellular parasite, such as T. brucei, is puzzling, because the majority of the organ consists of exocrine tissue that produces pancreatic enzymes for digestion, including trypsin and chymotrypsin, amylase, and lipase (Shi and Liu, 2014).…”
Section: Parasite Reservoirs and Pathologymentioning
confidence: 93%
“…Using a combination of bioluminescence and IVM, we confirmed that the g-WAT is a major parasite reservoir (Trindade et al, 2016), and we identified a previously unknown reservoir: the pancreas. Previous works on T. cruzi (Corbett et al, 2002;Dufurrena et al, 2017;Martello et al, 2013), Plasmodium (Abhilash et al, 2016;Glaharn et al, 2018), and Toxoplasma (Nassief Beshay et al, 2018) have reported sequestration in pancreatic blood vessels, pancreatic invasion, and morphological changes in the pancreas, including acute pancreatitis in humans. The fact that the pancreas represents one of the largest reservoirs of an extracellular parasite, such as T. brucei, is puzzling, because the majority of the organ consists of exocrine tissue that produces pancreatic enzymes for digestion, including trypsin and chymotrypsin, amylase, and lipase (Shi and Liu, 2014).…”
Section: Parasite Reservoirs and Pathologymentioning
confidence: 93%
“…The intensity of positive stained cells was graded as follows: 0 = negative; 1 = weak staining; 2 = moderate staining; 3 = strong staining. The total score (TS) for this immunohistochemical study was determined by obtaining the product of the percentage of positive cells and the intensity of the staining [22,23]. The sections were examined in a blinded manner, without prior knowledge of the patients, clinical status.…”
Section: Evaluation Of Immunohistochemistry Stainingmentioning
confidence: 99%
“…The intensity of positive stained cells was graded as follows: 0 = negative; 1 = weak staining; 2 = moderate staining; 3 = strong staining. The total score (TS) for this immunohistochemical study was determined by obtaining the product of the percentage of positive cells and the intensity of the staining [20,21]. The sections were examined in a blinded manner, without prior knowledge of the patients, clinical status.…”
Section: Evaluation Of Immunohistochemistry Stainingmentioning
confidence: 99%